O que o sujeito deseja quando recusa a escola? - Gustavo Alexandre Martins (2012)
This monograph originates from daily observations in the job of educational psychologist in public schools in Itabira MG. The discontent in education is present, among other situations, in groups of students identified for having an unique position which detaches from others.They are teenagers who, in spite of going regularly to school, are refractory to all educative measures, which results in discontentment in the professionals who work with them. That observation leads to a problem which opens this research: what does the subject desires whenhe refuses school? To answer this, we chose psychoanalysis as supporting theory, whose concepts have allowed us to operate the research subjects speech. S0 that we investigate the subject of the unconscious specifities, the adolescence dead locks, the concept of disavowal (Verleugmmg) and consequences of that mechanism of suspension of desire. That happens from Freudian texts and through contemporary authors, among which ee highlight Jean Jacques Rassial, Bernard Penot, Charles Melman and Jean Pierre Lebrun. The discussion is articulated with the field research conducted at four Itabira public schools, with psychoanalysis oriented interviews with teenagers who we suspect have been positioned through the disavowal (Verleugmmg). The speech similarities obtained from this material allowed us to build the idea that the teenagers have been established in a place of exception inschools, while singularities from two specific cases that have exceded from the others have indicated us signs of another position, possibly oriented through the disavowal (Verleugnung) mechanism.